PENGARUH DEMONSTRASI TERHADAP KETERAMPILAN KADER DALAM PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Wijaya, Ainur Rofi'ah Tiara; Milwati, Susi; Yulindahwati, Asworoningrum (Poltekkes Kemenkes Malang, 2024)
Breast cancer is not detected early because of the behavior of people who have never carried out BSE as much as 53.7%. This is due to the fact that respondents did not show significant interest in obtaining information about BSE steps and breast cancer. One of the primary preventions is by conducting a demonstration of BSE. The purpose of this study was to determine the effect of demonstration on cadres' skills in breast self-examination. The research design is pre-experiment with one group design, pretest, posttest design without control group. The results showed that almost all cadres (82.9%) had incompetent skills before the SADARI demonstration and after the SADARI demonstration all cadres had competent skills. It is hoped that cadres will be able to carry out BSE demonstrations and breast cancer early detection screening to the public.